Rapid discrimination of halal and non-halal pharmaceutical excipients by Fourier transform infrared spectroscopy and chemometrics - Nurul F A Razak; Roziah H Abd Karim; Jamia A Jamal; Mazlina M Said (Wolters Kluwer Medknow Publications, 2020)
Introduction: The appendage of "halal" to a product is not just a guarantee that the product is permitted for Muslims, but it has also become favorable lifestyle choice globally. However, the expansion of halal pharmaceutical market was hindered by lack of global halal standards for pharmaceutical ingredients and product integrity analytical methodology. Objective: This work aimed to explore the possibility of using Fourier-transform infrared (FTIR) spectroscopy and chemometrics to develop multivariate models to authenticate the "halal-ity" of pharmaceutical excipients with controversial halal status (e.g., magnesium stearate). Materials and Methods: The FTIR spectral fingerprints of the substance were used to build principal component analysis (PCA) models. The effects of different spectral pretreatment processes such as auto-scaling, baseline correction, standard normal variate (SNV), first, and second derivatives were evaluated. The optimization of the model performance was established to ensure the sensitivity, specificity, and accuracy of the predicted models. Results: Significant peaks corresponding to the properties of the compound were identified. For both bovine and plant-derived magnesium stearate, the peaks associated can be seen within the regions 2900 cm-1 (C-H), 2800 cm-1 (CH3), 1700 cm-1 (C=O), and 1000-1300 cm-1 (C-O). There was not much difference observed in the FTIR raw spectra of the samples from both sources. The quality and accuracy of the classification models by PCA and soft independent modeling classification analogy (SIMCA) have shown to improve using spectra optimized by first derivative followed by SNV smoothing. Conclusion: This rapid and cost-effective technique has the potential to be expanded as an authentication strategy for halal pharmaceuticals.